ANALISIS PENDAPATAN DAN TITIK IMPAS PRODUKSI GABAH KERING GILING (GKG) DAN BERAS DI KECAMATAN WASILE TIMUR KABUPATEN HALMAHERA TIMUR - Kaddas, Fatmawati; Ibrahim, Karmila; Muslikah, Muslikah (Universitas Khairun, 2022)
The development of food crops is part of the agricultural sector with the aim of realizing the conditions for meeting food needs with sufficient nutrition for the population to lead a healthy and productive life.Ã‚Â This study aims to determine the amount of income and the feasibility level of production of dry milled grain (GKG) and rice. This study was conducted in East Wasile District, East Halmahera Regency with sample determination using purposive sampling and systemic sampling on farmers in East Wasile District, East Halmahera Regency. The results of the study obtained were rice production income of Rp.21,068,283.78 and dry milled grain (GKG) production of Rp.22,134,104. The feasibility level in the production of dry milled grain (GKG) shows an R /C ratio of 2.1 and rice of 2.0, which means that both productions are feasible to be pursued because the resulting value1. Other feasibility indicators are BEP (Break-even point) where dry milled grain reaches breakeven or BEP Price as much as Rp.2,451 and BEP production is 644 Kg, while for rice to breakeven at the BEP value Price of Rp. 4,783 and BEP production of 387 Kg this means that farmers will not experience any gains or losses, so to be able to get a profit and not experience losses, the yield of dry milled grain and rice must be increased above the valueÃ‚Â BEP Production and BEP Price.Keywords: Income, Break-even point, Milled dry grain, Rice